2001
DOI: 10.1002/ijc.10345
|View full text |Cite
|
Sign up to set email alerts
|

Radiation effects on soluble metabolites in cultured HeLa cells examined by 1H MRS: Changes in concentration of glutathione and of lipid catabolites induced by gamma rays and proton beams

Abstract: SUMMARY Cultured HeLa cells were irradiated with a single acute dose of either gamma rays (40 Gy) or low-energy proton beams (20 Gy). 1H magnetic resonance spectra of intact cells harvested at different times after irradiation and of the correspondent perchloric acid (PCA) extracts prepared at different times after irradiation were run. Selected signals from glutathione and lactate were examined with the aim of investigating effects of irradiation on antioxidative stores and on mitochondrial activity. An incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 54 publications
(72 reference statements)
3
10
0
Order By: Relevance
“…The literature data report decrease of GSH level when cell density increases [9][10][11]. Our MRS data confirm the literature findings, as the relative concentration of GSH, G, decreased with time in culture in both MCF-7 and T98G cells (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The literature data report decrease of GSH level when cell density increases [9][10][11]. Our MRS data confirm the literature findings, as the relative concentration of GSH, G, decreased with time in culture in both MCF-7 and T98G cells (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…16,17 At the same time, the metabolomic technologies have contributed to a general understanding of how metabolites and their concentrations change under defined conditions.18 However, in contrast to transcriptomics and proteomics, broadbased metabolomic studies have not been used to analyze the cellular effects of IR. Smallscale, directed approaches using high-sensitivity nuclear magnetic resonance spectroscopy (NMR) [19][20][21][22][23] have been applied to estimate the relative concentration changes of a small subset of metabolites (e.g., reduced glutathione) following IR, but a global metabolomic approach has not yet been reported. The effects of IR include activation of stress responses to reduce reactive oxygen species (ROS), an increase in nucleotide pools for unscheduled DNA repair, and increases in cellular energy intermediates.…”
mentioning
confidence: 99%
“…In 2001, Grande et al . found that lactate of HeLa cells was increased 48 h after irradiation with high dose of gamma ray 55. Until recent years, with development of proteomic and genetic methods, the relationship between radiation and metabolism received more and more attention.…”
Section: Discussionmentioning
confidence: 99%